Financial regimes and uncertainty shocks - Piergiorgio Alessandri; Haroon Mumtaz (Queen Mary University of London, School of Economics and Finance, 2014)
Financial markets are central to the transmission of uncertainty shocks. This paper documents a new aspect of the interaction between the two by showing that uncertainty shocks have radically different macroeconomic implications depending on the state financial markets are in when they occur. Using monthly US data, we estimate a nonlinear VAR where economic uncertainty is proxied by the (unobserved) volatility of the structural shocks, and a regime change occurs whenever credit conditions cross a critical threshold. An exogenous increase in uncertainty has recessionary effects in both good and bad credit regimes, but its impact on output is estimated to be five times larger when the economy is experiencing financial distress. Accounting for this nonlinearity, uncertainty accounts for about 1% of the peak fall in industrial production observed in the 2007-2009 recession.
Keywords: C32; E32; E44; G0; 330; Uncertainty; Stochastic volatility; Financial markets; Threshold VAR